Numerical simulations of ultrathin CdTe solar cells with a ZnxCd1−xS window layer and a Cu2O hole transport layer - Amoupour, Ebrahim; Hassnzadeh, Javad; Abdolahzadeh Ziabari, Ali; Azimi Anaraki, P. (Journal of computational electronics, 2021)
CdTe solar cells are investigated using a solar cell capacitance simulator software. First, a conventional fluorine-doped tin oxide (FTO)/i-SnO 2 /CdS/CdTe structure is simulated using input experimental data to verify the simulation process. To make the cell more economical, the thickness of the CdTe layer is decreased, resulting in a degradation of the device performance. To decrease the minority-carrier recombination loss of the designed structure, a p -type Cu 2 O layer is exploited at the back contact as a hole transport electron blocking layer (HT–EBL). To address the performance degradation, a ZnS/CdS bilayer is used as the window layer. The interdiffusion of Cd into the ZnS due to annealing treatment and the formation of Zn x Cd 1− x S compound are also studied. Cell parameters include the thickness, doping concentration, and carrier lifetime are then optimized to enhance the power conversion efficiency (PCE). The proposed FTO/i-SnO 2 /Zn 0.5 Cd 0.5 S/CdTe/Cu 2 O configuration shows the best PCE of 17.5%, short-circuit current density ( J sc ) of 27.8 mA/cm 2 , open-circuit voltage ( V oc ) of 0.87 V, and fill factor of 72.34% under AM1.5G illumination.